Analisis Perkembangan Motorik Kasar Pada Balita Ditinjau Dari Status Gizi Di Posyandu Desa Ketimang Wonoayu - Kusumawardani, Paramitha Amelia (Akademi Kebidanan Bunga Husada Samarinda, 2023)
One of the components that influence gross motor development problems is nutritional status. The research method is quantitative with a cross-sectional research design. The population and sample are all children aged 3-5 years who are present at the posyandu in Ketimang Wonoayu as many as 31 toddlers with a sampling technique using total sampling in November 2022. Process data using univariate and bivariate analysis using the chi-square statistical test. The results of the chi-square test obtained a p-value of 0.006 <α (0.05), showing that there is a significant relationship between gross motor development and nutritional status for toddlers. The development of gross motor skills in toddlers in terms of nutritional status has an influence, so it is important for parents to pay attention to the nutritional status, especially at the age of five.